Carta de Roberto H. Todd a Luis Sánchez Vahamonte - Todd, Roberto H.; Sánchez Vahamonte, Luis (My University, 1935)
Escrituras de la casa a favor de la sucesión de Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Hernández Vizcovich, Jaime; Irizarry Rodríguez, Leo